Literature Review: Eksplorasi Etnomatematika pada Rumah Adat (Tongkonan) Tana Toraja - Suarti Djafar; Hafsyah Hafsyah; Rustiani S (Journal on Education, 2024)
Ethnomathematics is a field of study that connects mathematics with the culture of a specific community. In the context of Tana Toraja, the Tongkonan traditional house is a rich cultural representation imbued with mathematical values. This article summarizes research findings on the use of ethnomathematics in the architecture and symbols found in the Tongkonan traditional houses of Tana Toraja. The Tongkonan, the traditional house of the Toraja tribe in Tana Toraja, South Sulawesi, holds not only cultural and spiritual values but also significant archaeological importance. This research aims to identify the types of wood used in the archaeological components of Tongkonan at the Buntu Pune site, as well as to understand the techniques of selecting and using wood in this traditional construction. This study provides insights into how the Toraja people sustainably utilize natural resources and support the conservation of their cultural heritage.